Common Language of New Era in Sport Clubs: Emojis - Y ¼ce, Arif; AydoÄŸdu, Volkan; KatÄ±rcÄ±, Hakan (Jurnal The Messenger, 2021)
Defined as an easy and automated way of expressing emotions in the digital age, emojis are emerging as a new language in the social media world and sports clubs also. For sports clubs, it is of vital importance to communicate and establish effective relations with fans or followers. Hence, almost all professional sports clubs use social media and shape their social media accounts to interact with fans/followers and effectively maintain marketing communication efforts. The aim of this study was to determine the content of emoji usage in tweets of Turkish sports clubs (Besiktas JK, Fenerbahce SK, Galatasaray SK, Istanbul BaÅŸakÅŸehir FK, Trabzonspor SK). Since Twitter is one of the most heavily used social media networks of sports clubs, so in this study was preferred. Content analysis method was used to examine emojis used by sports clubs. The study found that sports clubs use emojis that create positive and neutral connotations. Emojis used are heavily determined to be visuals depicting the colors and symbols of sports clubs. The study is the first to examine sports clubs' emojis used. Hence, the study included important results for the management of communication and marketing strategies of sports clubs on social media.